PERAN KANTOR PERTANAHAN DALAM PENCEGAHAN SENGKETA DAN KONFLIK PERTANAHAN DI KABUPATEN BULELENG - I Gusti Ketut Riski Suputra; Ketut Sudiatmaka; Muhamad Jodi Setianto (Universitas Pendidikan Ganesha, 2023)
This research aims to find out and analyze the role of the Buleleng Regency Land Office in preventing land disputes and conflicts in Buleleng Regency, as well as knowing and analyzing the factors that cause the high number of land dispute cases in Buleleng Regency. In this research, the type of research used is empirical legal research using descriptive research characteristics. The data and data sources used are primary data and secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection techniques used are document study techniques, observation techniques and interview techniques. The sampling technique used was a non-probability sampling technique and the subject determination used a purposive sampling technique. Next, the data obtained is processed and analyzed qualitatively. The research results show that the role of the Buleleng Regency Land Office in preventing land disputes and conflicts in Buleleng Regency is through several work programs/annual work plans that are routinely carried out as well as prevention strategies in the form of strengthening cooperation and coordination with Government Agencies, Ministries/Institutions, Universities, APH, and other related stakeholders as well as the general public. Optimizing electronic technology information systems for land disputes, conflicts and cases for planning, policy analysis, handling and preventing land cases, mapping potential cases based on case typology and carrying out scientific/academic and practical studies on the causes of cases/root problems as well as resolution strategies and prevention of new cases. Meanwhile, the factors causing the high number of land dispute cases in Buleleng Regency are the ineffective coordination and cooperation between Ministries/Institutions and related parties in the context of handling the resolution and prevention of land cases; there is no appropriate and effective prevention mechanism regarding land cases in order to reduce the increase in land cases in the Buleleng Regency area; as well as the limited authority of institutions that intersect with the authority of other agencies. Apart from that, several other factors in society can also influence the percentage of land cases occurring in Buleleng Regency.